(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Azolla was a special fern that their associations with Anabaena azollae able to fix free nitrogen from air, to produce protein. Although by the ages, biota diversity those habits on the roots of Azolla increased and effected to protein concentration. The research was to find out population dynamics of biota on the roots of Azolla microphylla Kaulfuss and the growth peak. This study used Completely Randomized Design with 10 kinds of biota, i.e. bacteria, Fungi, Actinomycetes, Protozoa, Alga, Crustacean, Rotifers, Coelenterate, Insect and Molluscs, and it was used 3 replications. Research was conducted within 4 weeks and the populations of biota were observed every week. Data were statistically analyzed using Analysis Variant and Duncanâ€™s Multiple Range Test. The population dynamics of biota on the roots of Azolla microphylla Kaulfuss were influenced on its quantity and composition, and the growth peak is done in 2nd week. Â© 2001 Jurusan Biologi FMIPA UNS Surakarta Key words: Azolla, population dynamics, biota.